ChemInform Abstract: Visible‐Light‐Induced Regioselective Synthesis of Polyheteroaromatic Compounds. Issue 29 (29th June 2016) - Chatterjee, Tanmay; Choi, Myung Gil; Kim, Jun; Chang, Suk‐Kyu; Cho, Eun Jin
Abstract: A highly regioselective photocycloaddition of 2‐heteroarylanilines with heteroaryl alkynes gives polycyclic heteroarenes through diazotization.